Estudo e aplicação de eletrodo modificado com hexacianoferrato de óxido de rutênio para a detecção seletiva de sulfito - Montes, Rodrigo Henrique de Oliveira (2013)
This dissertation presents the electrochemical study of modified electrode with a ruthenium oxide hexacyanoferrate film aiming the selective and sensitive detection and quantification of sulfite in juice samples. First, electrochemical studies of the growth of ruthenium oxide hexacyanoferrate film on a glassy carbon electrode (working electrode) by cyclic voltammetry and electrochemical quartz crystal microbalance were performed. The electrochemical behavior of sulfite at the modified electrode was investigated and it was found that the electrochemical reduction of the molecule occurred at low potential (near to 0.0 V vs. Ag / AgCl / 3 mol L-1 KCl), which did not occurs at the unmodified electrode or even at a Prussian-blue modified electrode (iron hexacyanoferrate), which is indicative of classic electrocatalysis by the film and then it could be applied as a selective sensor for sulfite. Studies of the mechanism of mass transport of sulfite during the process of reduction at the modified electrode were conducted and the results indicate mixed processes for mass transport, in addition to the diffusional transport of sulfite from the bulk solution, it was found sulfite trapping inside the electrode film modifier. Thus, the electrochemical reduction of sulfite inside of the film is the likely cause of the decrease of the potential values close to 0.0 V. The modified electrode was applied for the amperometric monitoring at constant potential of -0.2 V using a batch system under constant stirring. This system provided a sensitivity of 41.5 nA L / mol (R = 0.996), a detection limit of 20 mmol L-1 and was free of interference from ascorbic acid, citrate, fructose and glucose. Subsequently, the same electrode was adapted into an electrochemical cell of \"wall-jet\" type for flow injection analysis (FIA), applying the constant potential of -0.2 V, for the determination of sulfite in concentrated juice samples. Also in the FIA system, it was evaluated the multiple pulse amperometry technique for the simultaneous determination of sulfite and ascorbic acid. A sequence of potential pulses was optimized (+0.4 V / 300 ms: oxidation of ascorbic acid; 0.0 V / 60 ms: electrochemical cleaning or maintenance of the electrode surface; -0.2 V / 60 ms: reduction of sulfite) was used for the simultaneous and selective determination of sulfite and ascorbic acid. The FIA method presented satisfactory repeatability (relative standard deviation for ascorbic acid and sulfite were 2.9% and 2.7%, respectively) and high analytical frequency (120 injections h-1). The analytical curve of both analytes presented acceptable correlation coefficient values (R = 0.998) and low limits of detection and quantification (2.9 and 9.6 μmol L-1 for sulfite and 7.6 and 25 μmol L-1 for AA, respectively).